Assessing and improving the biocompatibility of microfluidic artificial lungs. (August 2020) - Thompson, Alex J.; Ma, Lindsay J.; Major, Terry; Jeakle, Mark; Lautner-Csorba, Orsolya; Goudie, Marcus J.; Handa, Hitesh; Rojas-Peña, Alvaro; Potkay, Joseph A.
Abstract: Microfluidic artificial lungs (µALs) have the potential to improve the treatment and quality of life for patients with acute or chronic lung injury. In order to realize the full potential of this technology (including as a destination therapy), the biocompatibility of these devices needs to be improved to produce long-lasting devices that are safe for patient use with minimal or no systemic anticoagulation. Many studies exist which probe coagulation and thrombosis on polydimethyl siloxane (PDMS) surfaces, and many strategies have been explored to improve surface biocompatibility. As the field of µALs is young, there are few studies which investigate biocompatibility of functioning µALs; and even fewer which were performed in vivo . Here, we use both in vitro and in vivo models to investigate two strategies to improve µAL biocompatibility: 1) a hydrophilic surface coating (polyethylene glycol, PEG) to prevent surface fouling, and 2) the addition of nitric oxide (NO) to the sweep gas to inhibit platelet activation locally within the µAL. In this study, we challenge µALs with clottable blood or platelet-rich plasma (PRP) and monitor the resistance to blood flow over time. Device lifetime (the amount of time the µAL remains patent and unobstructed by clot) is used as the primary indicator of biocompatibility. This study is the first study to: 1) investigate the effect of NO release on biocompatibility in a microfluidic network; 2) combine a hydrophilic PEG coating with NO release to improve blood compatibility; and 3) perform extended in vivo biocompatibility testing of a µAL. We found that µALs challenged in vitro with PRP remained patent significantly longer when the sweep gas contained NO than without NO. In the in vivo rabbit model, neither approach alone (PEG coating nor NO sweep gas) significantly improved biocompatibility compared to controls (though with larger sample size significance may become apparent); while the combination of a PEG coating with NO sweep gas resulted in significant improvement of device lifetime. Statement of significance: The development of microfluidic artificial lungs (µALs) can potentially have a massive impact on the treatment of patients with acute and chronic lung impairments. Before these devices can be deployed clinically, the biocompatibility of µALs must be improved and more comprehensively understood. This work explores two strategies for improving biocompatibility, a hydrophilic surface coating (polyethylene glycol) for general surface passivation and the addition of nitric oxide (NO) to the sweep gas to quell platelet and leukocyte activation. These two strategies are investigated separately and as a combined device treatment. Devices are challenged with clottable blood using in vitro testing and in vivo testing in rabbits. This is the first study to our knowledge that allows statistical comparisons of biocompatible µALs in animals, a key step towards eventual clinical use. Graphical abstract: Image, graphical abstract